Opportunities in the Imposition of Legal Accountability Against Individuals Destroying the Environment Across Borders: Challenges and Barriers - Thohari, Ahmad Ahsin; Fauzan, Muhammad; Zaifa, Gilang Abi (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
Within the horizon of international law, individuals can only be held accountable if they commit violations of international criminal law as set out in the Rome Statutes. However, environmental destruction does not fall within the jurisdiction of the International Criminal Court to prosecute. On the other hand, environmental destruction is often attributed to the state as a subject of law, even though individuals who are the main perpetrators of environmental destruction cannot be held accountable internationally. This shows weaknesses in the international legal system in arresting and punishing individuals responsible for environmental damage across borders. The research method used is normative research with a legislative approach, in this study using several international provisions. The result of this study is that recognition of environmental destruction is very important, especially when the state is held accountable by other aggrieved countries. This accountability request can be brought to International Court of Justice with certain limitations. Through Article 5 of the Rome Statute, this recognition allows international courts to prosecute perpetrators of environmental destruction, so that law enforcement of environmental destruction can be carried out to the maximum. It is hoped that there will be an active role in Indonesia and the international community in responding to environmental destruction and making it as a 'Crime' special. Thus, international environmental law enforcement becomes more optimal and provides justice for all affected parties, both directly and indirectly.